2001
DOI: 10.1002/sia.964
|View full text |Cite
|
Sign up to set email alerts
|

Individual particle analysis for source apportionment of suspended particulate matter using electron probe microanalysis

Abstract: Suspended particulate matter (SPM) has a complicated system of emission and transport, and a receptor model is required for apportioning the sources of SPM. We have developed a method for individual particle analysis as a method of source apportionment using electron probe microanalysis (EPMA). In this method, elemental analysis of individual SPM particles is carried out using EPMA and the emission source of each is defined according to its x-ray spectrum. When many particles are analysed, cluster analysis is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…These metals could react with CO 3 2À to form metal-carbonate complex/minerals on the surface of calcitic or dolomitic crystals (Acosta et al 24 ). The possible sources of the Ca-rich particles are not only soil, but also cement, gravel (Vega et al 40 ), building materials (Kim et al 41 ), road paint and the pavement (Fukuzaki et al 42 ).…”
Section: Dust Propertiesmentioning
confidence: 99%
“…These metals could react with CO 3 2À to form metal-carbonate complex/minerals on the surface of calcitic or dolomitic crystals (Acosta et al 24 ). The possible sources of the Ca-rich particles are not only soil, but also cement, gravel (Vega et al 40 ), building materials (Kim et al 41 ), road paint and the pavement (Fukuzaki et al 42 ).…”
Section: Dust Propertiesmentioning
confidence: 99%
“…As the major mineral content for each fraction was similar across sample sites (Figure 6), irrespective of traffic density, as commonly occurs in other world roads dusts (e.g., [90][91][92]), it was deduced that there must be a unique source unrelated to traffic or land use for the most abundant minerals present in road dust (muscovite, anorthite, quartz, albite, calcite, chlorite, dolomite, and orthoclase). Some studies confirmed that there are inputs from surrounding soils and weathered rocks to the road surfaces [90,92,93]; nevertheless, other potential anthropogenic contributions, common in all roads (cement, gravel, building materials, road paint or degraded aggregates from asphaltic pavement [94][95][96]), cannot be ruled out. These common minerals also pose human health risk.…”
Section: Mineralogical Composition Of Fractionated Road Dustmentioning
confidence: 99%
“…However, there is no analytical method that can clarify the structure of individual BC particle, because the BC is very small. The individual particle analysis of other kinds of aerosol have been carried out using time-of-flight secondary ion mass spectrometry (TOF-SIMS) and energy dispersive X-ray spectrometry (EDS) with scanning electron microscopy (SEM) 4,5) . Figure 2 shows the SEM images of diesel soot particle at the same field of view before and after ESD with the acetone and water, respectively.…”
Section: Introductionmentioning
confidence: 99%